Utilization of Corporate Social Responsibility Funds for Improvement Community Welfare around the Mining Area of the Regency South Konawe - Ilham; Almansyah Rundu Wonua; Abdul Rahim Sya’ban (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Corporate Social Responsibility (CSR) is a form of corporate accountability addressing the social and environmental impacts resulting from operational activities, particularly for companies in natural resource sectors such as mining. CSR serves as a crucial instrument to promote the welfare of communities, especially those living near company operational areas. In South Konawe Regency, although many mining companies have implemented CSR programs, their implementation has not yet produced significant impacts on the welfare of the local communities. Objectives: This study aims to analyze the utilization of CSR funds to improve the welfare of communities surrounding mining operations in South Konawe Regency. Methods: A descriptive exploratory approach was employed with purposive sampling of mining companies across eight districts. Data collection techniques included questionnaires, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. Results: The findings indicate that the CSR programs currently implemented have not fully addressed the real needs of the community. There is a noticeable gap between program implementation and public perception of its benefits. Conclusion: Companies need to enhance the effectiveness of CSR implementation by adopting participatory, transparent, and needs-oriented approaches to ensure that the benefits are genuinely felt by the communities around the mining areas. Keywords: Corporate Social Responsibility, community welfare, mining, South Konawe, social impact, Indonesia